Transferring Juveniles To The Adult Court: A Factorial Survey Of Florida Prosecutors - King, Robin (2006)
Prosecutors have enormous discretion in the criminal justice system. Their decisions can ultimately impact and shape the course of the lives of the offenders whom they prosecute. This is certainly true for juvenile offenders considered for transfer to the adult court. Previous research indicates that serious, violent offenders are the most likely to be transferred to the adult court. However, very little is known on prosecutors' views of the role of the juvenile court, the process of transfer or the facts that influence their decision to transfer a juvenile to the adult court. A statewide survey of 800 Florida prosecutors was implemented using factorial vignettes. The results indicate that prosecutors support the idea of transfer generally, particularly when they are making the final determination to transfer to the adult court. Further, prosecutors indicate that juvenile transfer should be used sparingly, in extreme cases that are not appropriate to the resources of the juvenile court. The data were also examined to determine the effect of juvenile offender and juvenile offense characteristics on the decision to transfer a juvenile to the adult court. Analysis revealed several significant predictors of preference for transfer: age, threat to society, presence of a violent offense, ethnicity of juvenile, presence of prior adjudications, and amenability to treatment